Applied measurement of the motor speed controller for washing machine with random loads, part II - Khalid Mohammed; Jabbar A.F. Yahaya; Reyasudin Basir Khan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This research presents a very important industrial issue of controlling the production target, despite changing loads. Engines of various types, whether synchronous or synchronous, operate on single and three phase AC, DC motors or special motors such as stepper and servo. In all these motors, the speed control of the torque and speed of the above motors has gained considerable importance. There are three main ways reviewed in the current search, the second that completes the previous research referred to in the references. The three methods are PID method, LQR method and feeding –forward control methods. A real DC motor was used in electrical engineering machine laboratory at University of Diyala, Iraq. Where the actual parameters of the DC motor were actually calculated. The practical parameters were then integrated into the three control method Matlab codes for the purpose of comparing the results and representing the motor performance in the indicated control methods.